17. Effect of Fermented Moringa leaf (Moringa oleifera) powder in Feed To Increase Broiler Carcass Weight - Feri Hardiansah Manihuruk; Ismail Ismail; Rastina Rastina; Razali Razali; Mustafa Sabri; Zuhrawati Zuhrawati; Muhammad Jalaluddin (Jurnal Medika Veterinaria, 2018)
This study aimed to determine the effect of fermented kelor leaves (Moringa oleifera) flour as additive in animal feed to increase the weight of boiler carcass. The samples used were 28 DOC strain Cobb CP-707 aged 1 day. This study was conducted using one way pattern complete randomized design with 4 treatments and 7 replications. Control group (P0) was fed with commercial feed; P1 was given 5% fermented kelor leaves flour;  P2 was given 7,5% fermented kelor leaves flour; and P3 was given 10% concentration of fermented kelor leaves flour. Feed replacement was conducted on 08.00 am and 5.00 pm everyday, and water was given ad libitum. Chemical content of flour before and after fermented was analyzed at Research Centre of Biotechnology and Biological Resources, IPB. Body weight measurement was carried out at Veterinary Public Health Laboratorium. Data were analyzed using ANOVA with SPSS 16.0. Mean value (±SD) of carcass weight for P0, P1, P2, and P3 were 938,71±180,83, 1011,86±101,64, 1010,71±126,69, and 907,43±190,35, respectively. This study showed that adddition of fermented kelor leaves flour for 21 days did not affect (P0,05) the weight of broilers carcass.